Organising distribution : Hakonbolaget and the efforts to rationalise food distribution, 1940-1960 - Kjellberg, Hans (Handelshögskolan i Stockholm, Marknadsföring, Distributionsekonomi och Industriell Dynamik (D), 2001)
Organising is the general process by which we structure our world. It is a process that goes beyond social ordering by involving also the technical and the natural realms. Further, it is a process which involves us all. All the time. This dissertation focuses on the organising of business enterprise, more specifically, the organising of food distribution. It is study of formative events in the history of ICA, a major Swedish food distributor. The study provides a detailed account of the development of Hakonbolaget, one of four purchasing centres that formed ICA. Primarily, it accounts for Hakonbolaget´s efforts to establish a modern, rational food distribution system in the 1940s and 1950s. The thrust of these efforts was directed toward three areas of rationalisation: internal operations at the wholesale warehouses, retail operations, and wholesale-retail interaction. Incidentally, these were also central themes in the public debate about the growing costs of goods distribution in Sweden at the time. Through its efforts, Hakonbolaget realised a number of new solutions and established something of a model for modern food distribution. A model that came to characterise operation within ICA from the 1960s and well into the 1990s. Drawing on work within the sociology of science and technology, a conceptual vocabulary is developed for analysing the process of organising. This vocabulary suggests that organising can be regarded as a framing process – as attempts to define and realise sociotechnical situations. The inherent instability of such situations makes stability rather than change a puzzling observation. Consequently, change processes should be regarded as efforts to stabilise situations. Such efforts are closely linked to the establishment of metrics and the generation of representations. In addition to traditional social aspects of organising, the vocabulary also directs attention to the whole heterogeneous materials that surround us. === Diss. Stockholm : Handelshögsk., 2001